PENERAPAN PENDEKATAN PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA BERDASARKAN LEVEL SISWA - Husna Husna; Fona Fitry Burais (STAI Hubbulwathan Duri, 2019)
Problem-solving is a process or thinking activity to solve a problem. Mathematical problem-solving skillis needed for students both in the process of understanding mathematics itself and in everyday life. The problem solving can beachieved by implementingthe learning using a problem-solving approachwhich trains students to deal with various problems including individuals and group problemsto be addressed individually or together. This learning is oriented towards the investigation and discovery which is solving the problems. It is the basis for students to solve problems critically, systematically, logically, and creatively as well as the ability to collaborateeffectively and to present fundamental knowledge which in turn can improvethe solving skill. This study aimed to examine whether the improvement of mathematical problem-solving skillof students learned with the problem-solving approach wasbetter than students taught using the conventional learning. The improvement was examined based on the students’ levels. This study applied a pre-test and post-test control group design. The population of the study was Year 7 students of one of the junior high schools in Pidie, Indonesia, consisting of seven classes in 2017/2018.Two classes, a control, and an experimental class were selected as the sample through purposive sampling technique. The instrument used to obtain the data is the mathematical problem-solving skill test.The data was then analyzed by employing a two-way ANOVA test using SPSS. The results of the study showed that the improvement of mathematical problem-solving skill of the students learning with the problem-solving approach is better than the students experiencing the conventional learning, reviewed based on student levels. There is no interaction between the learning models and student levels on mathematical problem-solving skills. The resultsare expected to be used as a reference for mathematics teachers to apply the problem-solving approach in the learning process to improve mathematical problem-solving skills.